PERANAN GURU BK DALAM MEMBENTUK KONSEP DIRI (SELF CONCEPT) PESERTA DIDIK DI SMP NEGERI 11 PADANG - Yumilda, Fitri; Kasih, Fitria; Nofrita, Nofrita (Bimbingan dan Konseling, 2013)
Problems studied based on the phenomenon the researchers found in the field that is the learnirs who do not know about him unsure as to the ability based on the phenomenon that the researchers raised concerns about research: counseling teacher role in shaping the concept of self learners in SMP Negeri 11 Padang purpose of this study is to desceribe.1) counselor role inshaping the self concept of students from the aspects of khowledge.2) counselor role inshaping the sekf concept of students from aspects expectations.3) caunselor  teacher role ini shaping the self concept of students from aspects of the assessment. This research is a descriptive study sought to  describe the situation for what it is. The study population was all students in junior high school 11 Padang which amounts to 644 people. Techniques  in use ini sampling in each is proporrtional to the of 87 pople. Instruments used in this study was a questionnaire. While the use pf data analysis techniques for the percentage. The results of this study revealed that:1) counselor teacher role in shaping the self concept of students from the aspects of knowledge as much as 68,82% classified as good.2) counselor role in shaping the self  concept of students from aspect hope as much as 79,31% classified is exellent.3) counselor teacher role in shaping the self concept of students of the assessment as much as 62,07% classified is fair. Based on the results of the study authors suggest counselor in order to improve their perfomance to achieve the guidance and caunseling  services are affective and efficient to principals SMP N 11 Padang in order to assist and facilitate the work of guidance and counseling. STKIP PGRI in west Sumatera in order to better prepare prospective teachers with the knowledge and counseling skills a reliable.